Spanish medical supplies - Provisional (includes list of goods ordered) : inter-departmental correspondence - Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
1936-10-28 041-0134-003 292/946/41/134(iii)